Proprotein convertase subtilisin/kexin type 9 (PCSK9) in lipid metabolism, atherosclerosis and ischemic stroke. (2nd August 2016) - Zhang, Lingling; Song, Kangping; Zhu, Mengting; Shi, Jinling; Zhang, Huijuan; Xu, Liang; Chen, Yingzhu
Abstract : Proprotein convertase subtilisin/kexin 9 (PCSK9) is the ninth member of the proprotein convertase family. It is an important regulator of cholesterol metabolism. PCSK9 can bind to low-density lipoprotein receptors (LDLRs) and induce the degradation of these receptors through the endosome/lysosome pathway, thus decreasing the LDLR levels on the cell surface of hepatocytes, resulting in increased serum low-density lipoprotein cholesterol (LDL-C) concentrations. Recent studies have found that gene polymorphisms of PCSK9 are associated with hypercholesterolemia, risk of atherosclerosis, and ischemic stroke. Furthermore, monoclonal antibodies, peptide mimetics, small molecule inhibitors and gene silencing agents that are associated with PCSK9 are some of the newer pharmaceutical therapeutic strategies and approaches for lowering serum LDL-C levels. In this review, we will discuss recent advances in PCSK9 research, which show that PCSK9 is correlated with lipid metabolism, atherosclerosis, and, in particular, ischemic stroke. We will also discuss the current state of PCSK9 therapeutics and their potential in modulating these diseases.